(In)justice in Care for Children under Three Years of Age - Kristina Kalitová (Gender a Výzkum, 2022)
This article presents an analysis of the current (in)justice in childcare for children under three years of age in the Czech Republic by examining shifts in family and social policy after 1989. The paper compares three ways of redressing injustice: redistribution, recognition, and political representation in terms of domains of social injustice. Through the prism of Nancy Fraser's three-dimensional theory, the article analyses forms of redress in the economic, cultural, and political spheres. This approach aims to reveal the complexity of inequalities in childcare for children under three years of age and highlight the positive and negative aspects of family and social policy in the Czech Republic. The second goal of the paper is to establish a path towards amending the legislation that could change the legislation on family care in the Czech Republic based on a revision of values and the ideological and normative framework within which childcare for children under the age of three is understood in the Czech Republic.